PROMED – mail: an electronic mail disease-reporting: a case study (2005)
The early warning of disease outbreaks is a critical aspect of disease reporting, monitoring and surveillance at local, regional and international levels. Electronic mail (e-mail) provides a rapid, effective and increasingly accessible forum for disease outbreak reporting (and notification) worldwide. Drawing from their experience respectively as a subscriber and one of the three veterinary moderators to ProMED (the biggest e-mail early disease reporting forum in the world), the authors highlight the benefits of the medium for Nigeria (Africa). The use of ProMED forum for the confirmatory diagnosis of the 2001 epizootic of African swine fever (ASF) in pigs in Ibadan is a case at hand.